Gastrointestinal Candidiasis in Malnourished Children with Diarrhoea - Sunoto Sunoto; Suharyono Suharyono; Michael Gracey (Indonesian Pediatric Society, 1980)
It is known that the frequency of intestinal Candidiasis in infants and children below 3 years of age is very high, particularly in malnourished children. It has been shown also that Candida can reduce the absorption of sugar, water and electrolytes (Burke et al., I977; Thelen et al., I978). Recently we have studied the frequency of gastrointestinal Candidiasis and the Candida-killing-ability of leucocytes in Indonesian children. Species of Candida were found significantly more often in throat swabs, gastric, small intestinal contents and stools of malnourished children in comparison with specimens of reasonably well-nourished children. Furthermore there were marked qualitative differences in the species found in these groups according to their nutritional status. Studying the Candidacidal activity of leucocytes it shows that in malnourished children the killing-ability is significantly lower than in well-nourished children. These findings suggest that gastrointestinal Candidiasis may contribute to the pathogenesis of diarrhoea in malnourished children.